The Effect Of Compensation On Employee Performance Through Work Motivation As An Intervening Variable In PT. Anugrah Energitama Award East Kalimantan - Hutabarat, Joshua Tamara; Kuncono, Setio; Handayani, Sari; Nafisah, A'isy Fiklil; Endriatmoko, Yosa (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to find out and analyze the effect of compensation on employee performance through work motivation as an intervening variable in PT. Anugrah Energitama Award. The sample used in this study is employees of PT. Anugrah Energitama Award with a sample of 120 employees. The problem in this study is motivated by the importance of compensation as an external factor that can encourage motivation and improve employee performance. This study uses a quantitative approach with a survey method. Data was obtained through the distribution of questionnaires to employees of PT. Anugrah Energitama Award and analyzed using SmartPLS-based Structural Equation Modeling (SEM) technique. The results of the study show that compensation has a positive and significant effect on work motivation, as well as a direct effect on employee performance. Work motivation also has a positive and significant effect on employee performance. In addition, work motivation has been shown to play a role as a partial intervening variable in the relationship between compensation and employee performance. This means that compensation not only has a direct effect, but also indirectly through increased work motivation. This finding provides the implication that the management of PT. Anugerah Energitama needs to continue to improve a fair and competitive compensation system in order to foster work motivation and encourage the achievement of optimal employee performance.